Progenitor, environment, and modelling of the interacting transient AT 2016jbu (Gaia16cfr). Issue 4 (6th May 2022) - Brennan, S J; Fraser, M; Johansson, J; Pastorello, A; Kotak, R; Stevance, H F; Chen, T -W; Eldridge, J J; Bose, S; Brown, P J; Callis, E; Cartier, R; et al.
ABSTRACT: We present the bolometric light curve, identification and analysis of the progenitor candidate, and preliminary modelling of AT 2016jbu (Gaia16cfr). We find a progenitor consistent with a ∼ 22–25 M⊙ yellow hypergiant surrounded by a dusty circumstellar shell, in agreement with what has been previously reported. We see evidence for significant photometric variability in the progenitor, as well as strong H α emission consistent with pre-existing circumstellar material. The age of the environment, as well as the resolved stellar population surrounding AT 2016jbu, supports a progenitor age of >10 Myr, consistent with a progenitor mass of ∼22 M⊙ . A joint analysis of the velocity evolution of AT 2016jbu and the photospheric radius inferred from the bolometric light curve shows the transient is consistent with two successive outbursts/explosions. The first outburst ejected material with velocity ∼650 km s −1, while the second, more energetic event ejected material at ∼4500 km s −1 . Whether the latter is the core collapse of the progenitor remains uncertain. We place a limit on the ejected 56 Ni mass of <0.016 M⊙ . Using the Binary Population And Spectral Synthesis (BPASS) code, we explore a wide range of possible progenitor systems and find that the majority of these are in binaries, some of which are undergoing mass transfer or common-envelope evolution immediately prior to explosion. Finally, we use the SuperNova Explosion Code (SNEC) to demonstrate that the low-energy explosions within some of these binary systems, together with sufficient circumstellar material, can reproduce the overall morphology of the light curve of AT 2016jbu.